Facilitators and barriers to return to work and meet financial needs in parents of children with cancer. Issue 10 (28th July 2021) - Hjelmstedt, Sofia; Forinder, Ulla; Montgomery, Scott; Lindahl Norberg, Annika; Hovén, Emma
Abstract: Background: The aim of this study was to explore what facilitators and barriers parents of children with cancer identify for their ability to return to work and meet financial needs. Procedure: Nine focus groups (21 mothers; 11 fathers) were performed across Sweden in 2015 and 2019. A deductive content analysis approach was used. A preconstructed matrix consisting of 12 codes based on previous literature was used to organize the data. The codes were grouped into subcategories, which were abstracted to four generic categories. Results: Facilitators for a return to work were covered in the category "Flexibility and understanding from employers and social services, " and barriers in the category "Pressure to return without consideration of the consequences." Facilitators to meeting financial needs were covered in the category "Available public, private, and employer support, " and barriers in the category "Lack of organized and efficient support from employers and social services." Conclusions: The identified barriers suggest that there is room for improvement in the provision of psychosocial support, which relates to a perceived lack of organized support regarding practical, financial, and occupational matters. The results show a need for a coordinated support system that includes major stakeholders, such as the health care, welfare agencies, and employers. Moreover, employers should consider how to implement more workplace flexibility and involvement of occupational health services. Importantly, to be able to return to work and achieve a sustainable financial situation, it is necessary for all stakeholders to recognize the long‐term impact of parenting a child with cancer.